A study on the information needs and information seeking behavior of the Filipino elderly - Dalisay, Jerard Amir M. (School of Library and Information Studies, University of the Philippines Diliman, 2016)
The Filipino elderly are a marginalized sector of the society and some of their needs are being neglected. Access to information is vital to life in this day and age and accessing information has become a necessary life skill to deal with daily life challenges. The Filipino youth have less problems in information access as they are adept in technology use while the Filipino elderly are facing problems in accessing information because of their age and limited physical mobility. To help address this problem, this study investigated the information needs and information seeking behavior of the Filipino elderly.